2008
DOI: 10.1111/j.1750-3841.2008.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics of Listeria monocytogenes in Broth and Beef Frankfurters—Determination of Lag Phase Duration and Exponential Growth Rate under Isothermal Conditions

Abstract: The objective of this study was to develop a new kinetic model to describe the isothermal growth of microorganisms. The new model was tested with Listeria monocytogenes in tryptic soy broth and frankfurters, and compared with 2 commonly used models-Baranyi and modified Gompertz models. Bias factor (BF), accuracy factor (AF), and root mean square errors (RMSE) were used to evaluate the 3 models. Either in broth or in frankfurter samples, there were no significant differences in BF (approximately 1.0) and AF (1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 7 publications
1
75
0
2
Order By: Relevance
“…The modified Gompertz model is frequently used to interpret growth and inactivation curves of microorganisms under isothermal conditions (Bhaduri et al, 1991;Castro, Schmidt, & Penteado, 2007;Gibson, Bratchell, & Roberts, 1987;Huang, 2008;Uchima et al, 2008), and is expressed as:…”
Section: Mathematical Modeling and Fitness Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified Gompertz model is frequently used to interpret growth and inactivation curves of microorganisms under isothermal conditions (Bhaduri et al, 1991;Castro, Schmidt, & Penteado, 2007;Gibson, Bratchell, & Roberts, 1987;Huang, 2008;Uchima et al, 2008), and is expressed as:…”
Section: Mathematical Modeling and Fitness Evaluationmentioning
confidence: 99%
“…With regard to hurdles in foods, it has been observed that pH values equal to or lower than 4.4 can limit its growth, depending on the organic acid present and the constituent elements of the food itself (Beales, 2004;FDA, 2008;Huang, 2008). This microorganism can survive freezing temperatures as well as normal refrigeration temperatures.…”
Section: Introductionmentioning
confidence: 98%
“…The ability of the Linear-with-breakpoint (LIN) (Dantigny et al 2005), Baranyi and Roberts (BAR) (Baranyi et al 1993;Baranyi and Roberts 1994), and Huang (HUA) (Huang 2008) models (without upper asymptote) to describe the experimental data were assessed in this study. The LIN model was used to describe only the linear growth phase (Equation (1)).…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…The differential equations of the BAR and HUA original models were reduced so as not to consider the stationary growth phase (upper asymptote). For all models, D(t) is the colonies' diameter (mm) at the time t (day), µ max is the maximum growth rate (mm/day), λ is the adaptation time (day), and α (1/day) is an empirical curvature parameter, fixed as suggested by the author (α = 25) (Huang 2008).…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…The empirical sigmoidal type models such as the modified Gompertz and Logistic models or the biological-based Baranyi model have been used for fitting bacterial growth (Huang, 2008). However, data on the use of actual plant extract for inhibiting microbial growth and modeling the resulting kinetics is scarce.…”
Section: Introductionmentioning
confidence: 99%